TINJAUAN KRIMINOLOGIS TERHADAP TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) YANG TERJADI KELURAHAN ALAK, KECAMATAN ALAK, KOTA KUPANG - Bakker, Lex Stevkri; Leo, Rudepel Petrus; Dima Tallo, Daud (Petitum Law Journal, 2023)
The state of Indonesia is a state of law, constitutionally the statement that Indonesia is a state of law is contained in Article 1 Paragraph (3) of the Constitution of the Republic of Indonesia year 1945 which reads: “the state of Indonesia is a state of law”. With the development of Indonesian society today, the law in Indonesia is also required to be more advanced. It aims to maintain a balance between humans and the rules that govern their behavior. One form of Norm deviation (community disease) that is considered a social problem is trafficking in persons (traiffiking). The issues raised are: (1) What are the factors behind the occurrence of trafficking in persons in Alak Village, District Alak Kupang City? (2) How is the Modus Operandi carried out in Alak Village, Alak District, Kupang City? (3) How are efforts made to prevent the occurrence of trafficking in persons in Alak Village, Alak District, Kupang City? This research is an empirical legal research conducted in the East Nusa Tenggara police. The results of data processing were analyzed descriptively qualitative using inductive method. As well as the provisions contained in the applicable laws and regulations, both contained in the law of the Republic of Indonesia number 21 of 2007 concerning the eradication of trafficking in Persons (PTPPO). The results of this study indicate: (1) The occurrence of trafficking in Persons in the Village of Alak, Alak District, Kupang, ranging from family problems (environment), education and economic needs. (2) the usual Modus operandi of the perpetrator of the crime of trafficking in persons, such as the lure of a large salary, getting a decent job, being placed without a competency test and promised an invalid employment contract but with an offer of a favorable employment contract for the victim. (3) the police have made efforts to prevent the occurrence of trafficking in Persons in Alak Village, Alak District, Kupang city which are preemptive, preventive and repressive.